Enhancing EFL Students’ Recount Writing through Canva-Assisted Multimodal Learning: A Descriptive Qualitative Study at Junior High School Level - Asrul, Nurmahyuni; Sibarani, Berlin (EXCELLENCE: Journal of English and English Education, 2025)
This qualitative study examines the integration of Canva as a digital learning tool to enhance English as a Foreign Language (EFL) students’ recount writing skills at the junior high school level. The study was conducted at SMP Shafiyyatul Amaliyyah and involved 30 seventh-grade students engaged in Canva-based writing projects. Employing a descriptive qualitative research design, data were collected through classroom observations, semi-structured interviews, documentation of students’ written products, and open-ended questionnaires. Data analysis followed Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that Canva fostered higher student engagement, improved organization of recount texts, stimulated creative expression, and enhanced learners’ confidence in writing English. Although challenges such as limited internet access and vocabulary constraints were observed, Canva proved to be an effective pedagogical tool when supported by appropriate instructional scaffolding. This study contributes to EFL writing pedagogy by providing qualitative evidence on the role of digital multimodal tools in genre-based writing instruction.